nformative treatment and media competencies on COVID-19 in Ecuador - Mullo López, Alex (2021)
Information overload, misinformation and false news have led to the need to strengthen media literacy. With the global health emergency decree produced by the appearance of CoViD-19, users of traditional and digital media are in a constant search for information on the subject. This study analyzes the communication practices of media users and their perception of the information they receive about the coronavirus. To this end, quantitative research was done with the help of a self-administered questionnaire to a total of 2,090 Ecuadorians. In addition, use is made of the technique of reverse engineering of data to analyze the topics and traditional and digital platforms that citizens frequently access to get information. The results indicate that there is a preference for the information published on Web 2.0 platforms: topics related to health guidelines and a possible vaccine to face the disease. Also, a loss of confidence in traditional media and government sources is identified, while citizens give greater credibility to news shared by friends and family. Therefore, it is concluded that it is necessary to develop strategies focused on the diversity of social groups. This can be done by working among health organisms, scientists from Ecuadorian universities, media (traditional - digital) and citizen participation (prosumer) through interactive communicational proposals. These will make it possible to counteract the infodemic through media literacy and digital responsibility to position information based on scientific evidence.